Assessment, accountability and the literacy curriculum: reimagining the future in the light of the past. (1st March 2017) - Moss, Gemma
Abstract: This paper explores the dynamic to education system reform in England, highlighting the challenges the range of policy tools in use have created for policymakers, practitioners and researchers alike. Taking literacy policy in England as a 'telling case', I will argue that far from holding the answer to successful system reform, high‐stakes testing and the migration of system‐level data into the public domain create a series of challenges for politicians that they cannot satisfactorily solve. In turn, policymakers' attempts to manage the problems away are further compounding the difficulties teachers face. As policymakers' commitments to bringing about well‐motivated change waver, research and practitioner communities need to work more closely together to successfully reimagine a purposeful and engaged literacy curriculum for all.